The Prophets, the Priesthood, and the Image of God (Gen 1,26-27) - Middlemas, Jill Anne (Biblica, 2016)
This analysis considers aniconic rhetoric in Hosea, Second Isaiah, and Ezekiel, in order to assess commonality and difference with respect to prophetic and priestly perspectives of the divine image because interpreters draw on the prophetic literature in discussions of the thought of Gen 1,26-27. There is greater similarity in thought between Second Isaiah and Gen 1,26-27 as well as greater tension between Ezekiel and the first imago Dei passage than accounted for previously, and almost no commonality with Hosea. Furthermore, the prophets diversify the number and type of divine images as a means to resist idolatry